Schiff Base Anchored with Silver Nanoparticles as Effective Adsorbent for Removal of Cadmium(II) Heavy Metal from Industrial Wastewater - Sharma, Preeti; Uma, Vedula (Asian Journal of Chemistry, 2020)
The current study deals with the examination of the capacity of Schiff base anchored with silver nanoparticles for removal of cadmium(II) ions from industrial wastewater. Schiff base was synthesized using refluxing of salicylaldehyde and 4-aminoantipyrine in alcoholic medium. The characterization of Schiff base were studied by elemental analysis, FTIR, NMR, UV-visible and mass spectral studies. The silver nanoparticles were synthesized using the chemical reduction method and characterized. Then, silver nanoparticles anchored to the Schiff base by suitable method and again characterized. Peanut shells were used as solid phase for removal of Cd(II) ions. The effects of several parameters to optimize the adsorption of Cd(II) ions on solid phase, including pH, contact time, initial metal ion concentration and adsorbent weight were investigated. The maximum removal efficiency of Cd(II) ions on solid phase using Ag nano@Schiff base was achieved under experimental conditions of pH 6 (% removal = 81%), contact time of 15 min (% removal = 93%), initial metal ion concentration of 0.5 ppm (% removal = 95%) and adsorbent weight of 3 mg (% removal = 89%). The results showed that extraction of Cd2+ on AgNPs@Schiff base follows Freundlich adsorption isotherm.